Antibiotics alone versus appendectomy to treat uncomplicated acute appendicitis in adults: what do meta-analyses say?. Issue 1 (December 2015) - Rocha, Leonardo; Rossi, Felipe; Pessoa, Camila; Campos, Flavia; Pires, Carlos; Steinman, Milton
Abstract Background Primary appendectomy is the current standard of care for treating uncomplicated acute appendicitis, but interest in conservative treatment with antibiotics alone has been increasing in recent years. Clinical trials so far have shown controversial results. Methods A series of meta-analyses were reviewed. Studies comparing surgery versus antibiotics alone for treating uncomplicated acute appendicitis in adults were included. Descriptive statistics and data on treatment effects were retrieved and summarized. Results The conservative approach has a success rate of around 60 % and is associated with shorter pain duration, reduced analgesic medication, faster resolution of the inflammation process, lower expenses and quicker return to work. On the other hand, medical treatment leads to high (up to 20 %) readmission rates and more often requires surgery. An operative approach is associated with higher treatment success rates (>90 %) and very a low mortality rate. Conclusion Based on the current body of evidence, the use of antibiotics for primary treatment of uncomplicated acute appendicitis cannot be routinely recommended. Appendectomy remains the gold-standard treatment.